BENEFITTING STUDENTS WITH KNOWLEDGE-SHARING PRACTICES IN CULTURAL-BASED EDUCATION - Endin Mujahidin; Mas'udin Mas'udin; Alya Riani; Luthfi Fatia; Dini Puji Astuti (La Tansa Mashiro, 2022)
The majority of students in higher education find it challenging to understand cultural differences and communicate in English. In reality, students' enthusiasm wanes as a result of distractions like poor internet connections and challenging coursework. Using knowledge-sharing techniques in this situation is a solution to overcoming these challenges. The purpose of this study is to describe how students feel about using knowledge-sharing techniques in an online intercultural communication course. Three English Department students who participated in the research's Knowledge-sharing Practice in Intercultural Communication Learning at a university in Bogor were the main subjects of the study. Students in intercultural communication classes at higher education institutions range in age from 20 to 22 and academic standing. Focus groups discussion, interviews, and other forms of narrative inquiry were used in this qualitative study. This study discovered that implementing knowledge-sharing practices in online learning aids students in removing confusion from Intercultural communication classes, encourages higher education students to voice their opinions, aids higher education students in showing respect for cultural differences, stimulates students to think critically, encourages students to participate in the discussion, and inspires students to study abroad, but it is still challenging for them.